Orbital Teratoma: A rare congenital tumour - Khadka, Simanta; Shrestha, Gulshan Bahadur; Gautam, Pragati; Shrestha, Jyoti Baba (Nepalese Journal of Ophthalmology, 2017)
Background: Orbital teratomas are congenital, unilateral germ cell tumors, which are present at birth with moderate to massive proptosis. The rare tumour has to be managed individually and is at times difficult. Case: A female child in her 2nd day of life was brought to our department with complains of forward bulging of the left eye which was noticed since the time of her birth. Observation: Examination and investigations revealed a mass with scattered foci of calcification. The mass was causing expansion of left orbit with thinning and scalloping of bony boundaries of left orbit with no intracranial component. The scan suggests the diagnosis of orbital teratoma which was further confirmed by histopathological examination. Conclusion: The rare tumour presents a challenge in management. The aim of management depends upon the extent of tumour, preservation of vision whenever possible, promotion of normal orbital growth and cosmesis.